Extremal solutions for second-order fully discontinuous problems with nonlinear functional boundary conditions - Figueroa Rubén; López Pouso Rodrigo; Rodríguez-López Jorge (2018)
We provide new results concerning the existence of extremal solutions for a class of second-order problems with nonlinear functional boundary conditions where the nonlinearity considered may be discontinuous with respect to all of its variables. The main result relies on recent fixed point theorems for discontinuous operators and the lower and upper solution method.